Cyber Resilience Strategy: A Key guide to enterprise operations in digital age - Jitsupa Rittipalin (Journal of Digital Communications, 2021)
The objectives of this academic article aimed to study and analyze cyber threats affecting the organization and study the framework and strategies for cyber resilience. This qualitative and applied research was methodology. This study is documentary research that reviews the literature and research on the subject of cyber security, cyber threats, and cyber resilience. This paper was found that organizations now have faced a variety of cyber threats and need to adopt cyber resilience, i.e. be able to anticipant, detect, withstand, recover, and evolve in the face of cyber incidents. The suggestions for Thai corporates to cope with cyber threats are to establish a dynamic strategy for investing in cyber resilience, focus on responding to cyber-attacks at the policy level which, cyber security must be aware of at all levels of personnel, and develop the cyber-attack response personnel with Red team and Blue team countermeasure skill by stimulating and practicing with an attack scenario periodically.